Changes in training load, fitness, power and biochimical characteristics throughout professional rugby union season in back players - Dubois, R.; Paillard, T.; Chamari, K.; Maurelli, O.; Prioux, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Elite rugby game induces acute fatigue (inflammatory, catabolic states and muscle damages) which requires between 2 and 5 days to return to baseline level (McLellan, 2010). Furthermore, the game frequency and the duration of the competitive period may result in chronic fatigue illustrated by biochemical disturbances as well as a predominance of catabolic process (Banfi et al., 2006). Consequently, it appears essential to monitor and manage training load (TL) throughout a professional rugby season in order to optimize physical performance and reduce injury risk. Therefore, the aims of this study were quantifying TL throughout a professional rugby season and observed, in parallel, changes in physical performance and biochemical characteristics. Methods: Eight professional rugby union back players participated in this study. Weekly TL was assessed through 2 methods: S-RPE (Foster et al., 2001) and GPS technology (minimax S4, Catapult). Physical performances were evaluated by 5 YoYo recovery test level 2 (YYRT2) and 27 drop jump tests (DJ). Biochemical characteristics were assessed through three blood samplings were carried out in the first, the middle and the last part of the season. Results - Weekly TL (S-RPE) progressively decreased (p<0.001), especially due to a decrease (p<0.001) in training volume throughout the season. - External TL parameters (GPS) revealed a progressive reduction in total distance travelled (p<0.001). However, no significant change was observed for the high-speed running (HSR) distances, but the average speed of HSR significantly increased (p<0.001) over the season. - YYRT2 performances were not significantly changed during the season. - Negative significant correlations were found between training volume parameters and DJ (r=-0.49, p<0.001), whereas intensity parameters showed positive correlation (r=0.38; p<0.01). - The blood cell and reticulocyte concentrations significantly increased during the last part of the season (p<0.05). The cortisol concentration was also significantly increased (p<0.05).However, the testosterone/cortisol ratio was not significantly changed. Discussion: The TL decrease does not seem to affect fitness level, conversely, it may permit to optimize power production. Furthermore, this decrease may permit to avoid overreaching states (related to the biochemical state) likely to be induced by the accumulation of matches and training stress. It may also contribute to the final victory of the team studied.